THE EFFECT OF MARKET ORIENTATION AND ENTERPRENEURAL ORIENTATION ON BUSINESS PERFORMANCE WITH MARKETING CAPABILITIES AS A MEDIATION VARIABLE (CASE IN PUBLIC BANK OF MAKASSAR CITY) - Liliya Novita; Dian AS Parawansa; Jumidah Maming (Hasanuddin Journal of Applied Business and Entrepreneurship, 2020)
Business performance is an aspect that must be considered for the sustainability of a business. This type of research is quantitative research with SEM (Structural Equation Model) method that looks for relationships between variables. While the steps taken consisted of determining the structural model, followed by setting the measurement model, combining data and checking, pretest validity and reliability, determining the path analysis model, collecting models and analyzing with IBM-SPSS AMOS 23, testing the fit test model, if possible to re-checking the model, and then interpreting the results of data processing. The results showed that market orientation and entrepreneurial orientation had a positive and significant effect on marketing capabilities, marketing capabilities had a positive and significant effect on business performance, and, market orientation and entrepreneurial orientation does not have a positive and no significant effect on business performance.